Analisis Rendemen dan Skrining Fitokimia Ekstrak Cacing Laut Eunice siciliensis - Andi Evi Erviani; Abdur Rahman Arif; Nur Fahmiatun Nisa (Jurnal Ilmu Alam dan Lingkungan, 2019)
Sea worms have enormous potential to be used as alternative food ingredients because they have a fairly high protein content. The Research of the analysis yield and phytomomic compounds of Eunice Siciliensis marine worms has never been done. An effort to develop Eunice siciliensis sea worm-based alternative food ingredients is important to do phytochemical screening. This study aims to identify phytochemical compounds found in Eunice siciliensis marine worms and find out their benefits for health. This study was analyzed descriptively. The results showed that extract yield was 17.97% and Eunice siciliensis sea worm extract contained alkalaoid, flavonoids, saponins, triterpenoids / steroids, and tannins.